Prognostic Value of Thrombocytopenia in Myelodysplastic Syndromes After Hematopoietic Stem Cell Transplantation - Wang, Hong; Qi, Jiaqian; Li, Xueqian; Chu, Tiantian; Qiu, Huiying; Fu, Chengcheng; Tang, Xiaowen; Ruan, Changgeng; Wu, Depei; Han, Yue (Frontiers in Oncology, 2022)
Prolonged isolated thrombocytopenia (PT) is a common complication affecting the outcome of stem cell transplantation. In this study, we undertook a real-world study of 303 myelodysplastic syndrome (MDS) patients who received allogeneic hematopoietic stem cell transplantation (HSCT) between December 2007 and June 2018. 28.4% of MDS patients suffered from PT after HSCT. Survival analysis indicated that PT was associated with worse overall survival (OS) in MDS patients. The 2-year and 5-year OS in MDS patients with PT after HSCT were 49% and 47%, significantly worse than that of 68% and 60% in patients without PT (P=0.005). For RFS, patients with PT did not have an increased risk of disease relapse (P=0.964). After multivariate adjustment, PT was proved to be the independent risk factor associated with the worse OS (HR 1.49, 95% CI 1.00-2.21, P =0.048). We further analyzed risk factors associated with the occurrence of PT in MDS patients. Multiple logistic regression identified grade II-IV aGVHD, extensive chronic GVHD, hemorrhagic cystitis, and CMV activation as significant risk factors for developing PT. Among these variables, the Odds Ratio (OR) of grade II-IV aGVHD was the highest (P =0.001, OR: 2.65, 95% CI: 1.51-4.64). These data indicated the prognostic value of PT in MDS after HSCT. The identification of risk factors for PT may help improve patient management and lead to the design of effective treatment strategies.